Polyethyleneimine-Functionalized Magnetic Bagasse Composite for Efficient Adsorptive Removal of Yellow 4GL and Black R–S Dyes - Vu, Thi Thuy Hong; Bui, Thi Diem; Nguyen, Le Huu Khanh; Nguyen, Thi Hong Anh (Bulletin of Chemical Reaction Engineering & Catalysis, 2025)
Efficient removal of dye contaminants from wastewater remains a significant environmental challenge. In this study, a polyethyleneimine (PEI)-modified magnetic bagasse composite was synthesized by integrating sugarcane bagasse, PEI, Fe₃O₄ nanoparticles, and glutaraldehyde as cross-linking. The synthesized material was comprehensively characterized using SEM, BET, XRD, TGA, and FTIR techniques to elucidate its structural and physicochemical properties. Adsorption experiments were performed to investigate the effects of adsorbent dosage, initial dye concentration, pH, and contact time on the removal efficiency of Yellow 4GL and Black R-S dyes. The PEI-magnetic bagasse composite (PMBC) demonstrated impressive adsorption capacities of 185.19 mg/g for Yellow 4GL and 204.08 mg/g for Black R-S. The adsorption kinetics conformed to the pseudo-second-order model, indicating that chemisorption dominated the process, driven by electrostatic interactions and hydrogen bonding between the amino groups of PEI and the sulfonate groups of the dyes.